2008
DOI: 10.1016/j.bbr.2007.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neuronal nitric oxide reduces anxiety-like responses to pair housing

Abstract: Many psychological disorders are characterized by anxiety and alterations in social interactions. Recent studies demonstrate that the chemical messenger nitric oxide (NO) can regulate both anxiety and social behaviours. We tested whether an enzyme that produces NO in the brain, neuronal nitric oxide synthase (nNOS), serves as an interface between social interactions and anxiety-like behaviour. Several investigators have observed that mice increase anxiety-like responses in the elevated plusmaze after pair hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Our previous study showed that nNOS is essential for chronic stressinduced depression in mice . Very recently, several studies have indicated that NOS is involved in anxietyrelated behaviors (Miguel and Nunes-deSouza, 2008;Workman et al, 2008). In the present study, nNOS KO mice exhibited a markedly decreased latency to feed in NSF test, suggesting an anxiolytic-like phenotype.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Our previous study showed that nNOS is essential for chronic stressinduced depression in mice . Very recently, several studies have indicated that NOS is involved in anxietyrelated behaviors (Miguel and Nunes-deSouza, 2008;Workman et al, 2008). In the present study, nNOS KO mice exhibited a markedly decreased latency to feed in NSF test, suggesting an anxiolytic-like phenotype.…”
supporting
confidence: 64%
“…Our previous study showed that nNOS-derived NO contributes to chronic stress-induced depression . Recently, several studies suggest that nNOS may be related to anxiety-related behaviors (Miguel and Nunes-de-Souza, 2008;Workman et al, 2008). More importantly, nNOS plays a role in normal brain 5-HT function, especially in the 5-HT 1A and/or 5-HT 1B postsynaptic receptor function, and has significant implications for the psychiatric disorders characterized by aggressiveness and impulsivity (Chiavegatto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of nNOS diminishes anxiety-like responses to pair housing [57]. Also, anxiety-like behaviours in aged mice are recovered by modifying nNOS expression levels in the hippocampus or cerebellum [58].…”
Section: Mood Disordersmentioning
confidence: 98%
“…NO has multiple functions in nervous systems and has been implicated in the regulation of various behavioral, cognitive, and emotional processes (Gulyaeva and Stepanichev 1997;Lechman and Herman 2002;Wass et al 2008;Workman et al 2008). Recent findings have shown that the NOS inhibitors L-NNA, L-NAME, and 7-nitroindazole exhibit antidepressant-like properties in the FST, which are blocked by pretreatment with L-Arg (Jefferys and Funder 1996;Harkin et al 1999;Yildiz et al 2000;Joca and Guimaraes 2006).…”
Section: Discussionmentioning
confidence: 98%